Analisis Tingkat Harga Saham Perusahaan Manufaktur Sektor Industri Barang Konsumsi - Rofily Putriyandari (Universitas Islam Bandung, 2018)
Stock price is one of indicator the management successeda company determined by the number of requests and offers for the shares.The purpose of this research is to examine the effect of EPS, NPM, and SPP partially and simultaneously to stock price at manufacturing company of industrial sector of consumer goods listed in Indonesia Stock Exchangeperiod 2010-2015. The method used is quantitative method with descriptive verifikatif research type. The result of multiple linear regression analysis indicated that EPS, NPM, and SPP variables partially have a positive and significant effect to stock price,while the value of EPS, NPM, and SPP are significantly affect the stock prices. This research is changes of EPS, NPM and SPP partially or simultaneously will affect the stock price of manufacturing industry in consumer goods industry.Keywords: Earning Per Share, Net Profit Margin, Stock Price in the Past, Stock Price